2008
DOI: 10.1002/micr.20568
|View full text |Cite
|
Sign up to set email alerts
|

Is splenectomy a dyslipidemic intervention? Experimental response of serum lipids to different diets and operations

Abstract: After splenectomy, hyperlipidemia occurred with both diets. Preservation of the upper pole tended to correct dyslipidemia in modality A and to attenuate it in subgroup B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…As our model is an undernutrition steatosis model, 12,13 no significant differences were seen between groups in terms of blood lipids. However, according to previous reports using normal and high‐fat diets, splenectomy may worsen blood lipid metabolism 9–11 . This may also have developed due to an exacerbation of fatty liver changes by splenectomy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As our model is an undernutrition steatosis model, 12,13 no significant differences were seen between groups in terms of blood lipids. However, according to previous reports using normal and high‐fat diets, splenectomy may worsen blood lipid metabolism 9–11 . This may also have developed due to an exacerbation of fatty liver changes by splenectomy.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, rats fed a normal or high‐fat diet showed decreased HDL‐C and increased TG with splenectomy 10 . In a group of rats fed a normal diet or high‐cholesterol diet with subtotal splenectomy, correction of dyslipidemia was reported 11 . In other words, splenectomy may worsen lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of the relationship between the spleen and lipid metabolism have emerged: splenectomized rodents showed high cholesterol levels (21), hyperlipidemia (22), and increased intrahepatic fat accumulation (23). Elucidating the kinetics of iron in diabetes and other diseases is expected to lay the foundation for novel irontargeting therapies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed 13 , that rats submitted to splenic surgery and fed with a nutritionally balanced diet kept plasma lipid levels and hyperlipidemia occurred with the use of cholesterol-reducing chow and cholesterol-enriched diet in rats after splenectomy.…”
Section: Introductionmentioning
confidence: 99%